Military intervention as a spectacle? Authoritarian regionalism and protests in Kazakhstan. (2nd May 2023) - Libman, Alexander; Davidzon, Igor
Abstract : ASEAN's responses to Myanmar's membership illustrates that international organizations (IOs) face complex legitimacy challenges due to internal diversification. Heightened diversification destabilizes IOs' sources and claims of legitimacy. Abstract: Understanding the scope and the limits of cooperation of authoritarian regimes is important to assess their ability to support each other and strengthen authoritarian rule worldwide. While there is substantial evidence of authoritarian regimes working together to ensure mutual stability, autocracies are also notoriously mistrustful of one another. Therefore, they prefer to limit the assistance from other autocracies to rhetoric, to avoid the emergence of excessive dependencies. The conditions under which authoritarian cooperation goes beyond rhetoric, and even takes such extreme forms as military interventions, are insufficiently studied. The article investigates the case of the Collective Security Treaty Organization's (CSTO) intervention in Kazakhstan in 2022 as an example of an authoritarian regional organization sending a military mission to one of its member states. Using process tracing and carefully investigating the available evidence on the role of CSTO forces in Kazakhstan, we show that their intervention was more of symbolic importance than having an actual military role, and precisely for that reason it was acceptable to the leadership of Kazakhstan and other CSTO countries. The balance of power in central Asia (and in particular the role of China) ensured the credibility of commitment of the CSTO to keep its mission a symbolic one.